Exploring the factor structure of the adolescent form of the Francis Psychological Type and Emotional Temperament Scales (FPTETSA) among Canadian Baptist youth: full form and short form - Francis, Leslie J. (Mental health, religion & culture, 2024)
The Francis Psychological Type and Emotional Temperament Scales (FPTETS) operationalise the four components of the psychological-type model of personality alongside the fifth component of emotional temperament. The ten-item scales have been employed in research as continuous variables that explain individual differences in a wide range of religious beliefs and attitudes. The present study tested the factor structure of the adolescent form of the instrument (FPTETSA) and proposes a short form (FPTETSA-S) in which each of the five scales comprises six items, drawing on data provided by 360 Canadian Baptist youth. Both the full scales and the short scales are commended for use where the need is for continuous scale scores rather than generating psychological type categories.